Drumstick : a multi-purpose plant - Yadav, Lalu Prasad; Gangadhara, K; Rao, V V Appa; Singh, S; Saroj, P L (Indian Horticulture, 2019)
Traditionally, drumstick was used by people to prevent various physiological disorders, since it contains 7 times vitamin C than orange, 4 times more calcium than milk, 4 times more vitamin A than carrot, 2 times more protein than milk and 3 times more potassium than banana. Besides, it is rich in iron and antioxidants. In addition, it has tremendous potential on industrial features. Its roots are an alternate to horse radish; wood is used for making mats, paper and cordage manufacturing. The seeds are powdered and used as biowater clarifier; and non-rancid 38-40% oil extracted from seed kernels is used as lubricant in precision machinery and can also be used in the preparation of cosmetics and cooking.